Media społecznościowe jako ważny element komunikacji zewnętrznej organizacji sportowych = Social Media as an important element of sports organization external communication - Gajek, Katarzyna (Journal of Education, Health and Sport, 2016)
Gajek Katarzyna. Media społecznościowe jako ważny element komunikacji zewnętrznej organizacji sportowych = Social Media as an important element of sports organization external communication. Journal of Education, Health and Sport. 2016;6(9):44-57. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.155109 http://www.ojs.ukw.edu.pl/index.php/johs/article/view/3833 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Pola nd Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License ( http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016. Streszczenie Tym, co w istotnym stopniu wpłynęło na kształt procesów społecznych w ostatnich dwóch dekadach, jest wyłonienie się z tzw. nowych mediów, mediów społecznościowych, które w istotny sposób sprzęgły się ze strategiami komunikacji zewnętrznej organizacji sportowych różnego typu. Organizację działającą w branży sportowej wyróżnia nie tyle specyfika struktury lub funkcji kierowniczych a produkt. Sport, także ten rekreacyjny, stanowi specyficzną przestrzeń życia społecznego, która charakteryzuje się dużym znaczeniem wzajemnych interakcji pomiędzy organizacją a jej klientem. Oznacza to, że dla organizacji sportowej szczególne znaczenie ma właśnie komunikacja zewnętrzna, która nie tylko zapewnia łączność z klientem, ale tworzy również podstawę działalności każdej organizacji sportowej. Dlatego często poruszanym w literaturze przedmiotu zagadnieniem jest pytanie o sposób, w jaki organizacje sportowe wykorzystują w procesie budowania relacji z klientem oraz kreowania produktu najnowsze technologie komunikacyjne. Celem niniejszego artykułu jest jednak próba udzielania odpowiedzi zamiast na pytanie jak organizacje sportowe korzystają z mediów społecznościowych, dlaczego media te stały się dla organizacji szczególnie atrakcyjnym narzędziem w budowaniu sprawnej komunikacji organizacji sportowej z klientem. W artykule postawiono dwa pytania badawcze, które brzmią następująco: 1. Czym jest ekosystem mediów społecznościowych i co zatem odróżnia ekosystem, w którym funkcjonują media społecznościowe od takiego, w którym one nie istnieją? 2.Dlaczego media społecznościowe w dużym stopniu skolonizowały komunikację pomiędzy różnego typu organizacjami sportowymi a ich klientami? W pierwszej części pracy autorka skupia się na opisie i analizie ekosystemu mediów społecznościowych koncentrując się na elementach tego systemu oraz jego istotnych cechach dystynktywnych ukształtowanych przez nowoczesne technologie i zmiany kulturowe. W części drugiej zostaje podjęta próba wyjaśnienia specyficznego związku organizacji sportowych i mediów społecznościowych. Autorka w oparciu o literaturę z różnych obszarów dziedziny nauk społecznych – komunikologii i medioznastwa, antropologii, psychologii społecznej, zarządzania i marketingu, socjologii - oraz przykłady działalności wybranych organizacji stawia tezę, że głównymi elementami mającymi znaczenie dla silnego związku mediów społecznościowych ze sportem są: emocje, komunikacja ikoniczna, identyfikacja i narracja. Słowa kluczowe: media społecznościowe, organizacja sportowa, ekosystem mediów społecznościowych Abstract There is one thing that significantly contributed to shape social processes in the last two decades - the emergence of social media, which teamed up external communication strategies of various types sports organizations. Sports organization is distinguished by not so much the structure or function of management but a product. Sport becomes a specific area of social life, which is characterized by the importance of interactions between the organization and its customer what makes the organizational external communication particularly significant. Through vary channels sports organization provides communication with the client as well as builds the basis for persistence of each sports organization. The important question appears referring to this issue about the way in which sports organizations use the latest communication technologies in the process of building relationships with customers and co-creating the product. The purpose of this article, however, is an attempt to understand why social media have become particularly attractive tool in building efficient communication sports organization with the customer. There are two framing research questions asked: 1. What is a social media ecosystem and what is the difference between ecosystem with functioning social media in it and without them? 2. Why the social media settled the communication process between vary sports organizations and theirs customers? The first part of the article descripts and analyses the social media ecosystem by focusing on the elements of this system and its distinctive qualities shaped by modern technology and cultural changes. There is an attempt made to explain the specific compound sports organizations and social media in the following part of the article. The author basing on the literature and examples of activities of selected organizations argues that the main elements relevant to the relationship of social media and sport are emotions, iconic communication, visuals, identity and narrative. Keywords: social media, social media ecosystem, sports organization